IMPLEMENTASI AKTIVITAS CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN KALLA LINES DALAM PROGRAM KESELAMATAN BERLAYAR DI PULAU LAE-LAE KOTA MAKASSAR - Tenribili , Auliyah; Hadawiah, Hadawiah; Muttaqin Mustari , Andi (UNIVERSITAS MUSLIM INDONESIA, 2022)
A qualitative descriptive technique is employed in the research, and methods for gathering data include interviews, observation, and documentation. The Wisma Kalla Building and Lae-lae Island were the sites of this investigation throughout its one-month duration. The planning, execution, evaluation, and reporting stages of the CSR program have all been completed by the Kalla Lines firm, according to the study findings from that program's implementation. The results of the research from the implementation of the CSR program, namely the implementation of the four stages carried out by the Kalla Lines company, have been carried out, including the planning, implementation, evaluation, and reporting stages. In addition, there is the application of the Triple Bottom Line concept by the company in improving its image and providing space for stakeholders. As for the communication pattern that exists between Kalla Lines companies, namely the CSR program implementing committee as a communicator in conveying messages by saying information regarding facilities and infrastructure in the implementation of the CSR program, which will be carried out through direct and indirect communication, In this case, direct communication is visiting the implementation site and indirectly using a smart phone to contact the coordinator of the Lae-lae island community, Dg.H.Bahar. As a result, the community can well accept the concept of implementing CSR and is willing to provide facilities and infrastructure to make it easier for companies to carry out programs.